The Influence Of Country, Firm And Individual Factors On Knowledge Transfer Efficiency Among Chinese Multinational Corporations - Cheng, Junshuai (2022)
With the advent of the era of knowledge and information, knowledge management has become a concern of global corporations. Moreover, multinational Corporations (MNCs) played an increasingly important role in the development of the global economy. Knowledge transfer in MNCs has been one of the key challenges in the competitive era. However, from the summary and analysis of research on knowledge transfer in previous research, it easily found that the research issues were more one-sided and not profound. Especially, for China, with special culture and environment, the current research could not solve the practical problems. The main objectives of this study were to establish a completed framework and test the influencing factors of knowledge transfer efficiency in Chinese MNCs. Therefore, this study focused on the field of knowledge transfer in MNCs and used a holistic perspective to study the influencing factors on knowledge transfer efficiency.